2019
DOI: 10.1002/acr.23804
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Infrared Thermal Imaging to Detect Active Bone Lesions in Children With Chronic Nonbacterial Osteomyelitis

Abstract: Objective. Chronic nonbacterial osteomyelitis (CNO) is an autoinflammatory bone disease. An inexpensive and rapid imaging tool, infrared thermal imaging, was evaluated for its utility to detect active bone lesions in extremities of children with CNO.Methods. Children with suspected active CNO and healthy controls were enrolled. All subjects underwent infrared thermal imaging of the lower extremities. Patients in the CNO group also received a magnetic resonance imaging (MRI) examination. Hyperintensity within b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Studies have demonstrated that a number of bone and joint pathologies, for example arthritis and osteomyelitis, will affect the skin surface temperature measured at the site (Zhao et al, 2018, Lasanen et al, 2015. A limitation of this study is that the presence of underlying pathologies was not explored and there is therefore the potential that the patients recruited to the study may have had other undiagnosed pathologies, that may have had an effect on the results attained and may have caused an increase of temperature not attributed to the presence of sprain or fracture.…”
Section: Other Underlying Pathologymentioning
confidence: 99%
“…Studies have demonstrated that a number of bone and joint pathologies, for example arthritis and osteomyelitis, will affect the skin surface temperature measured at the site (Zhao et al, 2018, Lasanen et al, 2015. A limitation of this study is that the presence of underlying pathologies was not explored and there is therefore the potential that the patients recruited to the study may have had other undiagnosed pathologies, that may have had an effect on the results attained and may have caused an increase of temperature not attributed to the presence of sprain or fracture.…”
Section: Other Underlying Pathologymentioning
confidence: 99%
“…All volunteers were instructed not to eat heavy meals, smoking, drinking coffee, alcohol, or energetic stimulants for at least two hours prior to data collection [6] . The evaluation room, with a size of 10 m 2 was previously prepared for the acquisition, keeping the volunteer away from incidence sunlight and air flow, as well as electrical wires, to minimize the interference of infrared radiation from external sources [18] . Likewise, only the researcher and the volunteer remained in the room at the time of temperature measurement, thus minimizing the environment temperature change.…”
Section: Methodsmentioning
confidence: 99%
“…The medical room was maintained with a relative air humidity below 60%, assessed by a portable Mimipa ® thermohygrometer, and the ambient temperature, the patient was maintained at a comfort level of 22°C. Clothes covering the region of diagnostic interest were carefully removed and the patient was invited to attend clinical follow-up visits always wearing loose-fitting clothing that did not squeeze the affected limb, Zhao et al 23 The patient was instructed to not have heavy meals, smoke, or drink coffee, alcoholic or energetic stimulants for at least two hours before the appointment. If caffeinated beverages were consumed or antipyretic drugs were administered, the images were not collected during the medical consultation and the patient only underwent radiographic examination.…”
Section: Methodsmentioning
confidence: 99%